EFEKTIVITAS PENGGUNAAN INSTRUMEN PENILAIAN FORMATIF DALAM PROSES PEMBELAJARAN FIQIH KELAS XI DI MA RAHMATUL UMMAH NW DARUL HIJRAH - Suminah, Siti; Jinan, Muhammad Riyadlul; Anugerah, Adet Tamula (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to describe the effect of the Effectiveness of Using Formative Assessment Instruments in the Learning Process of Fiqh Class XI at MA Rahmatul Ummah NW Darul Hijrah in East Praya District, Central Lombok Regency. This research is descriptive quantitative research. Collecting data in this study using documentation and a Likert scale questionnaire which consists of variables of the effectiveness of the use of formative assessment instruments and fiqh learning variables. The sample of this study used the entire population of class XI as many as 19 students. Data processing in this study used Statistical Package For Social Sciences (SPSS) application. The results of testing hypotheses and simple linear regression analysis prove that the use of formative assessment instruments affects the fiqh learning process. Proven by the t test (t-count) of 8.381> 2.110 and the results of the R Square test analysis show that the use of formative assessment instruments has an effective effect on the fiqh learning process by 80.5%, which means that the more effective the formative assessment is, the more effective it is.